Mitigating Pass Gate Effect in Buried Channel Array Transistors Through Buried Oxide Integration: Addressing Interference Phenomenon Between Word Lines - Yeongmyeong Cho; Yeon-Seok Kim; Min-Woo Kwon (Applied Sciences)
As semiconductor devices become smaller, their performance and integration density improve, but new negative effects emerge due to the reduced distance between structures. In DRAM, these effects can lead to data loss or require additional refresh cycles, causing performance degradation. Specifically, in the 6F2 DRAM structure, activating a word line (WL) lowers the energy barrier of adjacent WLs, leading to the Pass Gate Effect (PGE). This study investigates the use of buried oxide beneath the WL to mitigate the PGE through simulation. Using SILVACO TCAD, we analyzed the impact of varying the size and position of the buried oxide on the PGE. The results showed that increasing the oxide size or reducing the distance to the WL effectively reduced the PGE. However, the presence of interface traps, which increase with the addition of buried oxide, was found to exacerbate the PGE, indicating that minimizing interface traps is crucial when incorporating buried oxide.